Strategi Kepala Madrasah Dalam Meningkatkan Kualitas Guru: (Studi Multi Situs di MTs. Al- Baitul Atiiq dan MTs. Al-Ittihad Kabupaten Ketapang Kalimantan Barat) - Hamzah, Akhmad Fauzi; Aliah, Rahimatul (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2023)
The head of the madrasa as the leader in the madrasa must have good management. The success of the madrasa depends on the head of the madrasa as a leader, if the head of the madrasa has ideas, creativity, good management and has a good strategy in improving the quality of the madrasa, of course the madrasa will get quality and be in demand by all people. This type of research includes field research and the data obtained in this research is data sourced from the field, and in this study the object of the MTs madrasah principal is. Al-Baitul Atiiq and MTs. Al-Ittihad in Ketapang Regency, West Kalimantan. The purpose of this research is to identify how the principal's strategy is to improve the quality of madrasas in MTs. Al-Baitul Atiiq and MTs. Al-Ittihad in Ketapang Regency, West Kalimantan. The data collection method used is observation which aims to obtain data about the state of the madrasa. The interview aims to obtain data about the strategies carried out by the head of the madrasa in improving the quality of madrasas as well as the formulation, implementation and evaluation in implementing strategies to improve the quality of madrasas. Documentation, aims to obtain MTs secondary data. Al-Baitul Atiiq and MTs. Al-Ittihad in Ketapang Regency, West Kalimantan. The results of the study show that in improving the quality of madrasas, Madrasah Principals MTs. Al-Baitul Atiiq and MTs.Al-Ittihad in Ketapang District, West Kalimantan, have their own strategies, being able to carry out leadership and teacher duties in accordance with government regulations. From the management and strategies used by each madrasa head, it can make madrasas of good quality both from an academic and religious moral perspective.